1970
DOI: 10.1038/bjc.1970.26
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of Breast Cancer in Middle and Late Age

Abstract: SUMMARY.-International rates of breast cancer for females aged 40-44 years (the " early " rate) and for females aged 65-69 years (the " late " rate) were positively correlated with sugar and fat intakes. The correlation explained three-quarters of the variation in the late rate, for 22 countries, but only half of the variation in the early rate. The late rate was, further, positively correlated with estimates of the percentage of nulliparous women (9 populations) and, together with terms for sugar and fat inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
3

Year Published

1971
1971
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 7 publications
0
20
0
3
Order By: Relevance
“…Additionally, several studies reported contradictory results. Although series of case-control studies failed to establish ABO blood groups as a major risk factor for breast cancer (Hems, 1970;Anderson and Haas, 1984;Dede et al, 2010), A group of authots (Tryggvadottir et al, 1988) reported that familial breast cancer cases had a 2-fold higher prevalence of blood group B than did the sporadic cases, and the frequency of this blood group in non-affected relatives of cases was significantly reduced. Moreover, another study has demonstrated that the absence of the Rh factor (Rh-) was positively associated with a 50% increased breast cancer risk (Ronco et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies reported contradictory results. Although series of case-control studies failed to establish ABO blood groups as a major risk factor for breast cancer (Hems, 1970;Anderson and Haas, 1984;Dede et al, 2010), A group of authots (Tryggvadottir et al, 1988) reported that familial breast cancer cases had a 2-fold higher prevalence of blood group B than did the sporadic cases, and the frequency of this blood group in non-affected relatives of cases was significantly reduced. Moreover, another study has demonstrated that the absence of the Rh factor (Rh-) was positively associated with a 50% increased breast cancer risk (Ronco et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to find environmental correlates of these disparate international incidence rates, investigators have examined differences in consumption of various foodstuffs, particularly animal fat, protein and refined carbohydrates, and have discovered significant positive correlations with breast-cancer mortality (Berg, 1975;Hems, 1970;Howell, 1975). Whilst these associations do not prove causality, the nutrition hypothesis appears to be plausible (Berg, 1975).…”
mentioning
confidence: 99%
“…In this report, we contrast the secular trend in the urban/ rural breast-cancer incidence ratio in the state of Iowa, U.S.A., with similar population-based trends in age-at-first-birth and nutritional data from available historical sources to gauge the relative importance of each factor in the changing breast-cancer incidence. Apart from studying total breast-cancer incidence, cases are also considered separately in selected age groups: "premenopausal" (ages 35-44) and "postmenopausal" (ages 65-74) as there is evidence that cancer in these groups behaves somewhat differently both biologically and epidemniologically (Hems, 1970). …”
mentioning
confidence: 99%
“…Authors reported that breast cancer incidence was similar among all ABO blood groups (Miao et al, 2013). In a study by Hems and Anderson, it was reported that A blood group was more commonly seen in patients with breast cancer (Hems, 1970;Anderson et al, 1985). In the study by Tryggvadottir et al, it was reported that B blood group type was 2 fold more common among cases with familial breast cancer when compared to sporadic cases (Tryggvadottir et al, 1988).…”
Section: Discussionmentioning
confidence: 99%